Elastoresistivity of Heavily Hole-Doped 122 Iron Pnictide Superconductors - Hong, Xiaochen; Sykora, Steffen; Caglieris, Federico; Behnami, Mahdi; Morozov, Igor; Aswartham, Saicharan; Grinenko, Vadim; Kihou, Kunihiro; Lee, Chul-Ho; Büchner, Bernd; Hess, Christian (Frontiers in Physics, 2022)
Nematicity in heavily hole-doped iron pnictide superconductors remains controversial. Sizeable nematic fluctuations and even nematic orders far from magnetic instability were declared in RbFe2As2 and its sister compounds. Here, we report a systematic elastoresistance study of a series of isovalent- and electron-doped KFe2As2 crystals. We found divergent elastoresistance on cooling for all the crystals along their [110] direction. The amplitude of elastoresistivity diverges if K is substituted with larger ions or if the system is driven toward a Lifshitz transition. However, we conclude that none of them necessarily indicates an independent nematic critical point. Instead, the increased nematicity can be associated with another electronic criticality. In particular, we propose a mechanism for how elastoresistivity is enhanced at a Lifshitz transition.